2007
DOI: 10.1063/1.2766846
|View full text |Cite
|
Sign up to set email alerts
|

Nanoindentation initiated dislocations in barium titanate (BaTiO3)

Abstract: Articles you may be interested inNanoindentation-induced plastic deformation and fracture behavior difference between a -and c -domains of BaTiO 3 single crystal J. Appl. Phys.Plastic behavior during loading of ferroelectric bulk materials is commonly explained by domain switching processes. In this study the authors show that dislocation induced deformation also occurs during nanoindentation of BaTiO 3 . Studies were conducted using a spheroconical shaped indenter together with observations using atomic force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Previous nanoindentation studies on different ceramics 32,[59][60][61][62] attributed the pop-in behavior to homogeneous dislocation nucleation because the maximum shear stresses in the experiments were far greater than the theoretical strength of the ceramic (~1.5-4 τ th ). As the magnitude of the maximum shear stresses in the present study is smaller than the theoretical strength of b-eucryptite, homogeneous dislocation nucleation likely does not occur.…”
Section: (1) Dislocation Nucleation and Kink Band Formationmentioning
confidence: 92%
“…Previous nanoindentation studies on different ceramics 32,[59][60][61][62] attributed the pop-in behavior to homogeneous dislocation nucleation because the maximum shear stresses in the experiments were far greater than the theoretical strength of the ceramic (~1.5-4 τ th ). As the magnitude of the maximum shear stresses in the present study is smaller than the theoretical strength of b-eucryptite, homogeneous dislocation nucleation likely does not occur.…”
Section: (1) Dislocation Nucleation and Kink Band Formationmentioning
confidence: 92%
“…The PFM image in Fig. 8 Therefore, to present both the cracks and 90°ac-domain structure simultaneously, the deflection image is used in this study. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8][9] Moreover, as the size of a ferroelectric device shrinks to the micro-and nanoscales, the mechanical properties and fracture behavior of individual domains become more and more critical for their practical function and reliability. In these applications, the material experiences combined mechanical and electrical loadings.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the initiation of dislocation motion always results in initiation of fracture in ceramics owing to their limited slip systems, and therefore dislocation-based macroscopic accumulation of large-scale plasticity at room temperature is limited in ceramics [13]. Recently, Ghosh et al [14] observed the existence of slip lines produced by indentation and scratch tests and manifested that dislocation mobility occurs in ZrB 2 .…”
Section: Introductionmentioning
confidence: 97%